Pemanfaatan Limbah Cangkang Kerang dengan Larva Black Soldier Fly menjadi Pupuk Organik di Desa Segorotambak - Muflikhatus Safaah Annawawi; Maudy Pratiwi Novia Matovanni; Muhammad Zainul Fata; Sandy Aulia Treeana (Institut Pertanian Bogor, 2026)
The accumulation of shellfish waste in Segorotambak Village due to increased seafood processing activities causes environmental problems such as bad odors, dirty environments, and polluting the coastal environment. The lack of education and understanding of the people of Segorotambak Village about processed shellshell waste products has resulted in a higher accumulation of shellfish waste. To overcome this problem, socialization and training in the manufacture of organic solid fertilizer from shellfish waste, organic waste, rice husk ash, and black soldier fly larvae (BSF) assistance as decomposition agents are important to be implemented. The implementation method includes coordination and surveys with village officials, socialization and training in making organic solid fertilizers, as well as evaluation of the effectiveness of socialization and training activities. The results of the evaluation from pre-test, post-test, and participatory observation showed that socialization and training activities succeeded in increasing the understanding of the Segorotambak village community to 94%. Cheap, easy to obtain, and simple methods cause this innovation to be easy to follow and apply by the people of Segorotambak Village. The socialization and training program for organic solid fertilizer innovation from shellfish waste not only plays a role in reducing the accumulation of organic waste, but also supports increasing soil fertility, strengthening community environmental awareness, and creating new economic opportunities.